Negotiation - Lewicki, Roy J. (McGraw hill, 2006)
Negotiation is a critical skill needed for effective management. "Negotiation, 5/e", explores the major concepts and theories of the psychology of bargaining and negotiation, and the dynamics of interpersonal and intergroup conflict and its resolution. It is relevant to a broad spectrum of management students, not only human resource management or industrial relations candidates.